Obstructive uropathy in canine: clinical case report - Pinilla León, Juan Carlos (2020)
The present study shows the case of a 7-year-old male canine who was admitted to the veterinary clinic "Vet Center", Bucaramanga, Colombia, for an alleged poisoning picture. The patient showed signs of depression, dysuria, strangury, haematuria and vomiting. Haematological assessment and urinalysis revealed a picture of dehydration and urinary infection. Blood chemistry showed insufficiency and postrenal azotemia, and the ultrasound examination showed the presence of a urolith and urinary bladder repletion, confirming the diagnosis of obstructive uropathy. For the stabilization of the patient, a Nelaton urinary catheter was placed to empty the bladder and hydro propulsion was done. Besides, maintenance intravenous solutions with 0.9% NaCl, antibiotics and anti-inflammatory were prescribed. Finally, cystotomy was performed to remove the urolith, in addition to a urethrostomy due to the recurrence of the obstruction.